SEXUAL HARASSMENT AND GENDER EQUALITY DIGITAL CAMPAIGN: EXPLORATORY ANALYSIS AND WEBSITE DEVELOPMENT - Ellwan Edy Wei; Muhamad Dody Firmansyah (P3M Institut Teknologi Pagar Alam, 2023)
This research was conducted to find out the effectiveness of a campaign website in helping support gender equality for men in terms of sexual harassment. The problem in this research is that there are rarely digital campaign websites to support gender equality and sexual harassment experienced by men. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development method as a guide in the design process. The website is then used to find out its usefulness and features by using the TAM (Technology Acceptance Model) by conducting in-depth interviews with 3 people using the purposive sampling method. Thus, it is hoped that this research will be useful as a reference or knowledge for future readers and researchers.